Improving Emotional and Cognitive Outcomes for Domestic Violence Survivors: The Impact of Shelter Stay and Self-Compassion Support Groups - Allen, Ashley Batts (Journal of interpersonal violence, 2021)
This study examined the effectiveness of a domestic violence shelter and tested the impact of a self-compassion support group curriculum on outcomes valued by shelters such as autonomy, emotional restoration, and safety. Data were collected from 251 women staying in a domestic violence shelter who had the opportunity to attend a self-compassion support group during their stay. Women completed a pre- and posttest survey assessing self-compassion, empowerment, positive emotion, and perceptions of safety. First, women experienced a positive change (N = 36) from pretest to posttest across all four outcome variables, suggesting the domestic violence shelter was effective at improving survivors’ well-being. Second, participants who attended a self-compassion support group at least once reported more positive posttest scores compared with those who did not attend a group (N = 79); however, this effect was limited to participants who stayed in shelter a short time. Women who stayed in shelter a longer amount of time experienced more positive posttest scores regardless of group attendance. Although the sample size was limited, analyses directly comparing the traditional shelter support group with the self-compassion support group show that both were equally effective. These findings provide support for shelter effectiveness in terms of improving well-being. They also suggest women who stay in shelter a short period of time may not experience as many shelter benefits unless they attend a support group. Therefore, shelters should consider offering support groups to women very soon after shelter entry. Furthermore, more research is needed to disentangle the benefits of self-compassion interventions over and above a general support group curriculum.